The nurse’s contribution to clinical research and evidence-based practice - Hamer, Susan (Henry Stewart Talks, 2017)
The nurses contribution to clinical research and evidence based practice, How to identify the evidence to support decision making, What are the sources of evidence and how to weigh its usefulness, How to get evidence into action -How to develop personal skills to support evidence based practice.